2017
DOI: 10.1590/1807-3107bor-2017.vol31.0029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of root dentin treatment on the push-out bond strength of fibre-reinforced posts

Abstract: Influence of root dentin treatment on the push-out bond strength of fibre-reinforced posts Abstract: This study evaluates the influence of root dentin treatment with NaOCl alone and combined with EDTA, with and without ultrasound activation, on the push-out bond strength (BS) of fiber-reinforced posts in weakened roots, cemented with RelyX or Panavia. The root canals of 42 maxillary canines were instrumented with Reciproc and 2.5% NaOCl. In the coronal 12mm of all canals, experimental weakening of the roots wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 42 publications
(48 reference statements)
2
19
0
14
Order By: Relevance
“…A n i n it i a l e le c t r on ic s e a r c h ide nt i f ie d 473 studies (Figure 1), and the hand searching process identified 2 studies 8,23 (total of 475 studies). The initial screening of the titles and abstracts resulted in 20 full-text papers that were read in full.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A n i n it i a l e le c t r on ic s e a r c h ide nt i f ie d 473 studies (Figure 1), and the hand searching process identified 2 studies 8,23 (total of 475 studies). The initial screening of the titles and abstracts resulted in 20 full-text papers that were read in full.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 9 included studies are summarized in Table 1. 8,17,19,23,24,25,26,27,28 Eleven studies that did not meet the inclusion criteria ( Figure 1) To investigate the effect of QMix irrigant compared with several other irrigating solutions on the bond strength of glass fibre posts to root dentine and on smear layer removal after post space preparation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations